Resilience Narratives and Negotiation of Space: A Multidimensional Analysis of the Bank Emok Phenomenon from Economic, Sociological, and Legal Perspectives - Deva Adelia; Yunisa Merdiana; Keysha Vania Putri Afriandi; Muhammad Rifqy; Yulianah Yulianah; Adang Sustisna (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines borrower characteristics, factors influencing debt decisions, economic pressure dynamics, the implications of joint liability systems for family resilience and negotiation of social space, and the juridical position of Bank Emok practices in Indonesia. Research Method: A Systematic Literature Review (SLR) with a descriptive-qualitative approach was employed by synthesizing 15 primary studies published between 2023 and 2025. Data were selected using predefined inclusion criteria and analyzed through content analysis and thematic synthesis. Results and Discussion: The findings reveal that Bank Emok borrowers are not exclusively from absolute poverty groups but also include economically vulnerable families with urgent liquidity needs and weak financial attitudes. Joint liability mechanisms intensify economic pressure and reshape domestic and community relationships. The review also indicates that Bank Emok borrowing often fails to improve long-term welfare and requires more nuanced juridical assessment. Implications: Strengthening financial literacy and expanding accessible formal microfinance alternatives are essential. Originality: This study integrates resilience narratives and negotiation of social space into the analysis of informal lending practices.